The popularity of skateboarding during the Olympic Games: will it reflect on its use as a means of urban transport in Brazil? (Research, Society and Development, 2022)
Introducing skateboarding as a sport in the 2020 summer Olympic Games sheds light on a practice usually marginalized, even in Brazil. To assess how Olympic Games' skateboarding impacted Brazilians' enthusiasm, this study analyzed search volumes on Google Trends and compared them with global data. After collecting and processing data, we identified that the average interest in skateboarding in Brazil before the Olympic Games was 4.5 times lower than the world average. During the event, Brazil was the country that most searched about skateboarding — a potential consequence of winning medals by Brazilian athletes. However, the growing popularity of skateboarding in Brazil evokes the difficulties that skateboarders face, such as the lack of regulation. The Brazilian Traffic Code does not recognize skateboarding as a vehicle, thus exposing users to risks on the roads.